Bridging the Self and its Identity Through the Works of Vikram Seth - Bidyasingh; PrasantaPadhi (International Journal of Psychosocial Rehabilitation, 2020)
Vikram Seth is one of the prominent writers in the modern age. He was born on 20th June, 1952. He is awarded several titles, such as Padma Shri, Sahitya Academy Award, Pravasi Bharatiya Samman, WH Smith Literary Award, and Crossword Book Award. His work portrays an Indian canon that vividly describes the beauty of the post-independence period. The works of Vikram Seth mainly deal with the idea of the search for self-identity. The major works of Vikram Seth are A Suitable Boy, The Golden Gate, An Equal Music, Mapping, and others, which majorly focus on the self and its search for true identity through dislocation. The plot contains different perspectives and ideologies. His works deal with the multiple frameworks of Seth’s artistry dealing with Indian culture, religion, family life, and post-colonial politics. The theories of the post-colonial attitude are also drawn from different perspectives like history, psychology, anthropology, political science, philosophy, and sociology. Seth’s interpretation of life is real and voluptuous. His works are more interesting because of his presence as narrator throughout this work. The paper highlights some of the major objectives, such as the institution of marriage, love and romance, and morals and ethics, and the socio-economic propagations, which also deal with the search for self-identity and individuality through a post-colonialism aspect. Post-colonialism is a historic era that depicts the consequences of the life and the circumstances of the people after colonialism. Seth’s works help in analyzing the enthralling facets of women. Also, it helps to find the nature and temperament of it.